Rootstock Incision Type and the Origin of Bud on the Scion Influence the Success Rate of Budding Propagation of “Rimau Gerga Lebong” Tangerine - Dhini, Debby R; Hermansyah, Hermansyah; Supanjani, Supanjani (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
The development of citrus crops is directed to produce tangerine plants that lead to substitute imported fruits by the development of budding seedlings technique using local varieties citrus. This research was conducted in November 2016 until March 2017 in citrus nursery of Horticultural Seed Center of Pematang Donok Village, Kabawetan Sub-district, Kepahiang Regency, Bengkulu Province. The research was arranged in a Completely Random Design with combination of two treatments, the first treatment was the origin of bud on the scion plant, they were E1 (upper part of the shoot scion), E2 (middle part of the shoot scion), E3 (basal of the shoot scion). The second treatment was cut type on the rootstock, they were J1 (H type), J2 (Forkert slice), J3 (T wedge). The treatment was repeated three times, so there were 27 experimental units. Each experimental unit consisted of 10 liners, so there were 270 liners of the experiment. The result of this research showed that incision types of H model and Forkert model, as well as the bud originated from the middle and the basal part of shoot scion were good to support the success rate of budding propagation of Rimau Gerga Lebong (RGL) tangerine.